A Novel Hexavalent Capsular Polysaccharide Conjugate Vaccine (GBS6) for the Prevention of Neonatal Group B Streptococcal Infections by Maternal Immunization. (19th February 2019) - Buurman, Ed T; Timofeyeva, Yekaterina; Gu, Jianxin; Kim, Jin-hwan; Kodali, Srinivas; Liu, Yongdong; Mininni, Terri; Moghazeh, Soraya; Pavliakova, Danka; Singer, Christine; Singh, Suddham; Handke, Luke D; et al.
Abstract: Background: Group B streptococcus (GBS) causes serious diseases in newborn infants, often resulting in lifelong neurologic impairments or death. Prophylactic vaccination of pregnant women prior to delivery could provide comprehensive protection, as early onset and late-onset disease and maternal complications potentially could be addressed. Methods: Capsular polysaccharide conjugate vaccine GBS6 was designed using surveillance data yielded by whole-genome sequencing of a global collection of recently recovered GBS isolates responsible for invasive neonatal GBS disease. Capsular polysaccharides were isolated, oxidized using sodium periodate, and conjugated to CRM197 by reductive amination in dimethyl sulfoxide. Immune responses in mice and rhesus macaques were measured in a multiplex Luminex immunoglobulin G (IgG) assay and opsonophagocytic activity assays. Results: The optimized conjugates were immunogenic, alone and in combination, in mice and rhesus macaques, inducing IgG antibodies that mediated opsonophagocytic killing. Active immunization of murine dams with GBS6 prior to mating resulted in serotype-specific protection of pups from a lethal challenge with GBS. Protection following passive administration of serotype-specific IgG monoclonal antibodies to dams demonstrated conclusively that anticapsular polysaccharide IgG alone is sufficient for protection. Conclusions: The findings support the ongoing clinical evaluation of maternal GBS6 vaccination as a potential alternative method to prevent GBS disease in infants. Abstract : Six-valent capsular polysaccharide conjugate vaccine GBS6 for the prevention of neonatal Group B Streptococcal (GBS) infections was evaluated in preclinical models. Vaccination with GBS6 or administration of serotype-specific IgG to pregnant dams protected pups against lethal challenges with GBS.